Sex-Specific Platelet Activation Through Protease-Activated Receptors Reverses in Myocardial Infarction. Issue 1 (January 2021) - Soo Kim, Beom; Auerbach, David S.; Sadhra, Hamza; Godwin, Matthew; Bhandari, Rohan; Ling, Frederick S.; Mohan, Amy; Yule, David I.; Wagner, Larry; Rich, David Q.; Ture, Sara; Morrell, Craig N.; et al.
Abstract : Objective: The platelet phenotype in certain patients and clinical contexts may differ from healthy conditions. We evaluated platelet activation through specific receptors in healthy men and women, comparing this to patients presenting with ST-segment-elevation myocardial infarction and non-ST-segment-elevation myocardial infarction. Approach and Results: We identified independent predictors of platelet activation through certain receptors and a murine MI model further explored these findings. Platelets from healthy women and female mice are more reactive through PARs (protease-activated receptors) compared with platelets from men and male mice. Multivariate regression analyses revealed male sex and non-ST-segment-elevation myocardial infarction as independent predictors of enhanced PAR1 activation in human platelets. Platelet PAR1 signaling decreased in women and increased in men during MI which was the opposite of what was observed during healthy conditions. Similarly, in mice, thrombin-mediated platelet activation was greater in healthy females compared with males, and lesser in females compared with males at the time of MI. Conclusions: Sex-specific signaling in platelets seems to be a cross-species phenomenon. The divergent platelet phenotype in males and females at the time of MI suggests a sex-specific antiplatelet drug regimen should be prospectively evaluated. Abstract : Supplemental Digital Content is available in the text.